Is it Who You Ask or How You Ask? Findings of a Meta-Analysis on Genetically Modified Food Valuation Studies - Astrid Dannenberg (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper presents a meta-analysis of 46 primary studies reporting a total of 108 genetically modified food valuation estimates. The analysis shows that elicitation methods and formats used in the primary studies affect valuation estimates much more than do sample characteristics. Moreover, consumer aversion to genetically modified food seems to have increased over time. Previous findings are confirmed that consumer valuation strongly depends on the type of food product and varies among regions.
Keywords: Q18; Q51; Q55; 330; meta-analysis; consumer preferences; genetically modified food; Novel Food; Konsumentenverhalten; Meta-Analyse; Statistische Erhebung; Welt